Synergistic bactericidal activity of a ginsenoside-copper nano-agent against gram-positive and gram-negative biofilm bacteria - Tan, Tao; Chang, Weiyi; Wang, Yihan; Cheng, Ran; Yang, Dongsheng (Frontiers in Microbiology, 2026)
BackgroundBiofilm-associated infections pose a formidable challenge due to their high tolerance to conventional antibiotics. While copper-based therapies offer a promising avenue, their clinical utility is severely limited by non-specific cytotoxicity and rapid deactivation. To address this, we engineered an intelligent, redox-responsive nanoplatform composed of Ginsenoside Re (GS) and copper (Cu2+), termed GSR NPs.MethodsGSR NPs were synthesized through a facile self-assembly process using GS and Cu2+. The nanoparticles were extensively characterized using microscopy and molecular dynamics simulations. Their physicochemical stability, redox-responsiveness, reactive oxygen species (ROS) generation, and antibacterial efficacy were evaluated against S. aureus and E. coli. Additionally, biofilm disruption capabilities and in vitro biocompatibility were assessed.ResultsCharacterization indicated the formation of uniform, ultra-small nanospheres stabilized by coordination and hydrogen bonds. GSR NPs remained stable in physiological buffers but exhibited responsive behavior in reducing microenvironments, triggering the release of active components and ROS generation. Consequently, GSR NPs displayed potent antibacterial activity and effectively disrupted established biofilms of both S. aureus and E. coli, far surpassing the efficacy of individual components. Mechanistic investigations suggest a multi-pronged attack involving physical disruption, oxidative stress induction, and metabolic suppression. Furthermore, the nanoparticles demonstrated favorable biocompatibility with negligible cytotoxicity toward mammalian cells in vitro.ConclusionThis work presents GSR NPs as a highly efficient and potentially low-toxicity antibacterial strategy. By overcoming the limitations of free copper ions, GSR NPs offer a promising therapeutic alternative for combating challenging biofilm-related infections.